Incidental thyroid carcinoma - Abdul Jabbar, Mohammed Q.; Mutlak, Nofel Sh.; Abdul Hussein, Waleed; Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: thyroid carcinoma is the most common endocrine carcinoma as it accounts for almost 90% of all endocrine malignancies. The term incidental denoted malignant tumors of the thyroid gland detected by post-operative biopsy results of the resected specimens resected from benign thyroid diseases. Among the incidental thyroid malignancies, papillary carcinoma is the commonest pathological type.Objectives : To determine the incidence of incidental thyroid carcinoma and to insist on accurate preoperative diagnostic work up of patients with thyroid diseases.Patients & Methods: A prospective study, which was conducted during the period from March 2013 to April 2014 at Baghdad teaching hospital first surgical unit by the same team of surgeons. Ninety nine patients were referred for surgical treatment of goiters, 4 patients who had a known malignant diagnosis by FNAC were excluded from the study, the remaining 95 patients were evaluated for the presence of the cancer by post-operative pathological exam. The surgical operations performed were total lobectomy with isthmusectomy, subtotal, near total or total thyroidectomy.Results: incidental thyroid carcinoma was found in 18 patients (18.9%), 15 patients with non-toxic MNG (15.7%), 2 patients with solitary thyroid nodule (2.1%) and one patient (1.1%) with toxic MNG. Out of 18 patients with incidental thyroid carcinoma, 15(83.3%) aged >45 and the remaining 3 (16.7%) aged≥45, only one male had ITC and the remaining patients were females.Conclusions: It can be concluded that the incidence of incidental thyroid carcinoma in our study is relatively high so a more radical surgical treatment in the management of patients with presumably benign thyroid disease is recommended.